Direct radiation-induced effects on dental hard tissue - Hui Lu (Radiation Oncology, 2019)
Abstract Background Radiation caries is a complication of radiotherapy characterized by enamel erosion and dentin exposure. The mechanisms of characteristic radiation caries formation are not well-understood. The aim of this study was to evaluate the direct radiation-induced effects on dental hard tissue and investigate their role in the formation of radiation caries. Methods Sixty non-carious third molars were divided into three groups (n = 20), which would be exposed to 0 Gy, 30 Gy, and 60 Gy radiation, respectively. After radiation, microhardness and elastic modulus were measured at four depths by means of a Vickers microhardness tester and atomic force microscopy (AFM). The microstructure was observed by scanning electron microscopy (SEM). X-ray diffraction and Raman microspectroscopy were used to determine crystal properties and protein/mineral (2931/960 cm− 1) ratios. Results A statistically significant decrease in microhardness and elastic modulus values 50 μm from the dentino-enamel junction (DEJ) in enamel was revealed in the 30-Gy and 60-Gy groups. With the increasing dose, destruction of interprismatic substance and fissures at the DEJ-adjacent region were found. A greater reduction of crystallinity was revealed in enamel compared with dentin. Raman spectroscopic analysis showed a slight increase of the protein/mineral ratio for enamel following accumulated radiation, while the protein/mineral ratio for dentin was decreased. Conclusions Radiation could directly alter the mechanical properties, micro-morphology, crystal properties, and chemical composition of dental hard tissue. The early destruction of DEJ-adjacent enamel, combined with decreased crystallinity of enamel under radiation exposure, may be related to the formation of characteristic radiation caries.